RISK MANAGEMENT AND STERILIZATION PROCESS IN MEDICAL DEVICE INDUSTRY (Global Journal of Advanced Engineering Technologies and Sciences, 2021)
FMEA is a structured method to study a design or process that anticipates and minimizes unwanted performance or unexpected failures. FMEA is primarily a qualitative technique and is considered a “bottom-up” technique, as individual aspects of risk are analyzed separately and combined. Reusable devices are contaminated with microorganisms after the use of medical devices. To overcome these risks, “reprocessing” is carried out. As per the manufacturer’s instructions, all medical devices must be reprocessed before use. In this paper, we will describe the FMEA, Risk management process, and different types of sterilization and cleaning steps. It will give an overview of medical device remediation of risk management and sterilization process